The EFFECT of MISTAKE UNDERSTANDING For LEGAL TEXTS on The SOCIETY (Al-Khawarige Model) - Ibrahim, Mohammed (Islamic Sciences Journal, 2023)
Praise is to Allah, the Lord of the Worlds, and peace and blessings is upon his best creation, and the seal of his prophets and messengers of our Prophet Muhammad, peace be upon him and his companions. This is a summary of the research that I want to initiate, the Comprehension mistake of the legal texts and its impact on the community, and I am taking the Khawarij as sample. extremists as a model. The purpose of the study is to shed light on the negative effects of wrong reasoning on society and to show that the elements of the eternal message of Islam require a sober and wise approach stemming from the logic of prudent or rational reason, wisdom, moderation, tolerance and balance, and away from extremism, and all the factors of demolition, weakness and myths. Accordingly, the scientific material imposed on the research to be based on an introduction, a preamble, and three investigations, followed by a conclusion. Praise be to Allah, the Lord of the Worlds, and peace and blessings be upon his sincere and faithful messenger, and on the machine and his companions.